EFEKTIVITAS MODEL PEMBELAJARAN KOOPERATIF TIPE TEAMS GAMES TOURNAMENT (TGT) BERBANTUAN MEDIA KARTU SOAL PADA SUB MATERI IKATAN KOVALEN KELAS X MIA DI SMA ISLAM HARUNIYAH PONTIANAK - Zulfadhli Abdillah (Jurnal Ilmiah Ar-Razi, 2018)
This  study  is  motivated  by  the  low  learning  outcomes  in  the  Sub-covalent  Bond class of tenth-grade students, SMA Islam Haruniyah Pontianak. This problem is due to the  lack  of  students'  understanding  of  the  concept  of  Covalent  Bonds.  Therefore,  a proper learning model is required to improve students’ understanding of Covalent Bond concepts  based  on  the  characteristics  of  both  learning  materials    and  students.  This study  aimed  to  investigate  the  differences  in  the  student  learning  outcomes  and  the effectiveness of the question card-based on TGT learning in the Sub-covalent Bonding material. Using the pre-experimental method of one-group pretest-posttest design, the tenth-grade  students  of  Math  and  Science  Class  of  SMS  Islam  Haruniyah  Pontianak participated in this study. The data collection tools used were learning outcomes tests, observation sheets, and interview sheets. The results of data analysis revealed that the average  pretest  score  was  36  and  the  posttest  was  62.94.  In  addition,  the  t-test statistical  analysis  indicated  a  significance  value  of  0.00  (0.00  <0.05)  which  meanth that there were differences in student learning outcomes between before and after the question  card-based  TGT  learning  model  implemented.  The  gain  value  was  0.42.  In other words, the  question card-based on TGT learning model is effective in improving the student  learning outcomes with good category. Keywords: Covalent Bond, Question Card, Team Games Tournament (TGT)